Analisis Biomekanika Gerakan Atlet Renang untuk Optimalisasi Latihan - Wijono Sukaputra Agussalim; Trifena Ruth Clara (Jurnal Pengabdian Dian Mandala, 2025)
This study aims to analyze the effect of body angle variations on propulsion force, drag coefficient, and freestyle swimming performance using a biomechanical approach. The background of the study is based on the importance of movement efficiency in swimming which greatly affects athlete performance. The research method used a quantitative experimental design involving university or club level swimmers who have a minimum of three years of training experience. Subjects were selected through purposive sampling with the criteria of being healthy, accustomed to using freestyle techniques, and willing to follow the research procedure. The instruments used included 3D motion capture to record body angles and movement coordination, force sensors to measure propulsion force and drag coefficient, and a time recording system to calculate average speed. The research procedure was carried out by providing variations in body angles of 0°, 15°, and 30°, each with three replications. The data obtained were analyzed using descriptive statistics to describe the average, standard deviation, and data distribution, as well as comparative statistics (ANOVA or paired t-test) to compare performance between angle variations. The results showed that a 15° body angle provided optimal performance, characterized by increased average speed and propulsive efficiency compared to 0° and 30° body angles. These findings confirm that body angle regulation is a key factor in reducing water resistance and increasing propulsive effectiveness. The discussion of the results indicates that applying biomechanical analysis to swimming training can provide objective information for developing training techniques and strategies. Therefore, this study concludes that a 15° body angle is the most ideal position for improving freestyle swimming performance. Further research is recommended to expand the number of subjects, explore variations in other swimming styles, and integrate physiological data to obtain a more comprehensive picture.